A novel planar dual polarized millimetre wave antenna for KU band applications - B, Sowjanya; V Saiteja, G; Krishna, Mrudhvi; Krishna, M; Bhagavan, A (International Journal of Engineering and Technology, 2018)
A dual polarized antenna array to operate in Ku band is analysed and designed. Cross polarization is the major factor considered. The second requirement is the uni-layer fabrication used for any vertical interconnection accesses. Circular microstrip patches are chosen as the radiating elements. The antenna is fed through the two orthogonal linear edges and shown in microstrip line pattern. Reduction of sidelobes is doneÂ  by using dolphchebychev distribution. scattering parameters procedure is done to get efficient stimulation. The properties of antenna array simulation are fixed over a bandwidth having center frequency 500MHz. Hence proven, showing that a cross polarised antenna is used for ku band frequencies or millimeter wave applications. The design procedure and parameters are explained clearly to utilize the fact that the antenna array could be reduced.Â